The Analysis of Regional Income on Economic Growth Lampung Province - Miswan Gumanti; Fauzi Fauzi; Citrawati Jatiningrum (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The important indicators in economic growth are financial performance and regional finance. This study aims to provide empirical evidence of the role of regional income and financial performance on economic growth, and economic growth as an indicator of community welfare in an area. Design/methodology/approach: This study uses panel data analysis to test the regression model. Findings: The findings reveal that regional income and economic performance on economic growth have an influence on the level of community welfare in Lampung Province, but the evidence proves that regional levies are not significant on community welfare. Practical implications: This study also provides evidence that the regional retribution is not significant, so that the regional retribution has a value that has not been able to improve welfare in the of Lampung province. Paper type: Research article